2001
DOI: 10.2134/jeq2001.3041184x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nitrate Leaching in Irrigated Agriculture

Abstract: The impact of improved irrigation and nutrient practices on ground water quality was assessed at the Nebraska Management System Evaluation Area using ground water quality data collected from 16 depths at 31 strategically located multilevel samplers three times annually from 1991 to 1996. The site was sectioned into four 13.4‐ha management fields: (i) a conventional furrow‐irrigated corn (Zea mays L.) field; (ii) a surge‐irrigated corn field, which received 60% less water and 31% less N fertilizer than the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 24 publications
6
84
0
1
Order By: Relevance
“…The lower ICUC values in the 90s than in the 00s were due to the already indicated changes in irrigation infrastructures and management. Hence, as found in other studies (Bonati and Borin, 2010;Cavero et al, 2011;Spalding et al, 2001), a key strategy to reduce N export loads is the improvement of irrigation performance. In the case of VID, each 10% increase in ICUC, above 40% ICUC, will decrease N export loads by 31 kg N/ha (Figure 5c).…”
Section: Relationships Between N Exported In Vid Irrigation Return Flsupporting
confidence: 53%
“…The lower ICUC values in the 90s than in the 00s were due to the already indicated changes in irrigation infrastructures and management. Hence, as found in other studies (Bonati and Borin, 2010;Cavero et al, 2011;Spalding et al, 2001), a key strategy to reduce N export loads is the improvement of irrigation performance. In the case of VID, each 10% increase in ICUC, above 40% ICUC, will decrease N export loads by 31 kg N/ha (Figure 5c).…”
Section: Relationships Between N Exported In Vid Irrigation Return Flsupporting
confidence: 53%
“…This suggests that a switch to sprinkler irrigation can be used to achieve regulatory compliance with no further interdiction required. These results confirm those of Spalding et al [2001]; on Nebraska test plots they found that sprinkler irrigation reduced nitrates in groundwater and could be used to maintain nitrate levels at 10 ppm. Furrow irrigated fields, by comparison, required more irrigation water, more nitrogen fertilizer, and increased groundwater nitrogen levels.…”
Section: Discussionsupporting
confidence: 82%
“…This supports recommendations from previous detailed research efforts as part of the USDA Management Systems Evaluation Area project, which had a study site within the CPNRD-GWMA from 1990 to 1996. In the Management Systems Evaluation Area project, Spalding et al (2001) found that a combination of conversion from furrow to sprinkler irrigation, accompanied with N fertigation, significantly reduced N leaching. As part of the Conservation Effects Assessment Project evaluation, a survey was conducted in 2008 of producers in CPNRD-GWMA Phase 1, 2, and 3 areas to evaluate their current use of certain practices.…”
Section: Additional Considerationsmentioning
confidence: 99%